Comparison of Operational Efficiency of Banks Syariah and Banks Conventional Based on Data Envelopment Analysis Method - Yusuf Agustian, Mochamd Ferdy (Arbain Publishing, 2024)
This research aims to compare operational efficiency between Islamic banks and conventional banks using the Data Envelopment Analysis (DEA) method. Islamic banking has continued to grow rapidly in recent years, but still faces its own challenges compared to conventional banking, especially in terms of operational efficiency. With a qualitative approach through literature studies and library research, this research examines various factors that influence the efficiency of the two banking systems. The DEA method is used to measure the relative efficiency of selected Islamic and conventional banks, by analyzing input-output ratios such as operational costs, profitability and service quality. The research results show that although Islamic banks operate based on profit sharing principles and syariah-compliant contracts, their level of operational efficiency is often comparable to conventional banks. However, there are several factors such as asset management and operational costs that have been identified as areas requiring improvement in Islamic banks. This research also discusses the implications of these findings for policy makers and banking institutions, and highlights the need for Islamic banks to adopt stronger strategies to increase efficiency and competitiveness. The contribution of this research is to provide a deeper understanding of operational dynamics in Islamic banking, as well as offering recommendations for bridging the efficiency gap between Islamic and conventional banks. Future research could further examine the impact of technological advances and regulatory frameworks on the operational efficiency of these two banking systems.